Enhanced Surveillance for Histoplasmosis—9 States, 2018–2019. (17th August 2020) - Benedict, Kaitlin; McCracken, Stephanie; Signs, Kimberly; Ireland, Malia; Amburgey, Victoria; Serrano, Jose Antonio; Christophe, Natalie; Gibbons-Burgener, Suzanne; Hallyburton, Sara; Warren, Kimberly A; Keyser Metobo, Alison; Odom, Racheal; et al.
Abstract: Background: Histoplasmosis is often described as the most common endemic mycosis in the United States, but much remains unknown about its epidemiology among the general population. Methods: We conducted enhanced surveillance in 9 states during 2018–2019 by identifying cases through routine surveillance and interviewing 301 patients about their clinical features and exposures. Results: Before being tested for histoplasmosis, 60% saw a health care provider ≥3 times, and 53% received antibacterial medication. The median time from seeking health care to diagnosis (range) was 23 (0–269) days. Forty-nine percent were hospitalized, and 69% said that histoplasmosis interfered with their daily activities (median [range], 56 [2–3960] days). Possible exposures included handling plants (48%) and bird or bat droppings (24%); 22% reported no specific exposures. Only 15% had heard of histoplasmosis before their illness. Conclusions: Histoplasmosis can be severe and prolonged. Additional educational efforts to increase public and provider awareness and reduce delays in diagnosis are needed.